2021
DOI: 10.1108/ijqrm-05-2020-0171
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validation of an instrument for measuring problems with performance appraisal of automotive parts manufacturing employees

Abstract: PurposeTo develop and validate an instrument to measure the problems associated with performance appraisal.Design/methodology/approachThe implementation was in two phases. Phase 1 involved the development and validation of an instrument to measure the problems with performance appraisal. Phase 2 involved the exploration and confirm the construct measurement. Data used in Phase 1 were collected from interviews with administrators and employees in the automotive parts manufacturing industry and five experts. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…However, unfairness often occurs, especially in performance appraisal through problems with the appraisal process and problems with the appraising person [31]. These problems affect attitudes and behavior.…”
Section: Theories For Explaining the Concepts And Study Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…However, unfairness often occurs, especially in performance appraisal through problems with the appraisal process and problems with the appraising person [31]. These problems affect attitudes and behavior.…”
Section: Theories For Explaining the Concepts And Study Frameworkmentioning
confidence: 99%
“…Na-Nan et al [31] studied problems with performance appraisal based on the theory of justice and the problems with performance appraisal concepts. Exploratory factor analysis found that the problems with performance appraisal can be divided into two components.…”
Section: Problems With Performance Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Rubio et al (2003, p. 94), "Content validity refers to the extent to which the items on a measure assess the same content or how well the content material was sampled in the measure". Numerous studies by Gerbing and Anderson (1988), Farooq (2017), Dar and Mishra (2019) and Na-Nan et al (2021), defined content validity as the judgemental procedure in which an attempt is made to determine whether your instrument includes those behaviours that are relevant to the domain. In the present study, items included should be expressed unambiguously and exhibits imperative characteristics of diabetes-related awareness instrument (DRAI).…”
Section: Methodsmentioning
confidence: 99%